2021
DOI: 10.1038/s41598-021-91309-w
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 sequences in lentiviral vector genomes can be substantially reduced without compromising transduction efficiency

Abstract: Many lentiviral vectors used for gene therapy are derived from HIV-1. An optimal vector genome would include only the viral sequences required for transduction efficiency and gene expression to minimize the amount of foreign sequence inserted into a patient’s genome. However, it remains unclear whether all of the HIV-1 sequence in vector genomes is essential. To determine which viral sequences are required, we performed a systematic deletion analysis, which showed that most of the gag region and over 50% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Lentiviral (LV) vectors used for gene therapy are predominantly derived from Human Immunodeficiency Virus type 1 (HIV-1). Two components are needed to make a virus-based gene delivery system: first, the packaging elements, encompassing the structural proteins and the enzymes required to generate an infectious particle, and second, the vector itself, that is, the genetic material transferred to the target cell [ 194 ]. The viral coding sequences are usually removed from the viral backbone and replaced by the gene of interest, such as the CAR.…”
Section: Vector Backbonementioning
confidence: 99%
“…Lentiviral (LV) vectors used for gene therapy are predominantly derived from Human Immunodeficiency Virus type 1 (HIV-1). Two components are needed to make a virus-based gene delivery system: first, the packaging elements, encompassing the structural proteins and the enzymes required to generate an infectious particle, and second, the vector itself, that is, the genetic material transferred to the target cell [ 194 ]. The viral coding sequences are usually removed from the viral backbone and replaced by the gene of interest, such as the CAR.…”
Section: Vector Backbonementioning
confidence: 99%
“…Although a low functional titre is not unusual for lentiviruses (it has been estimated that as few as 1% of HIV virus particles are capable of infection (4)), this must be improved in order to facilitate cost-effective, large-scale manufacturing of lentiviral gene therapies. An important cause of non-functional lentivirus is the presence of incomplete lentiviral RNA, which can occur for a range of reasons such as anomalous splicing, premature transcription termination at cryptic polyA sites or insufficient processivity of the polymerase due to the length of the construct (3)(5). In addition to lowering the infectious titre, this may reduce therapeutic efficacy due to an incomplete transgene and can also pose a safety risk due to loss of safety elements such as chromatin insulators or other regulatory components designed to limit the potential for oncogene activation (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to have an assay in place that can identify not only the abundance, but also the causes of lentiviral RNA truncation. RNA sequencing using Illumina (3) and Nanopore direct cDNA (5) approaches have both been used to demonstrate improvements to lentiviral vectors, and sequencing has also been applied to other therapeutics, such as mRNA vaccines (7). However, there is currently no clear consensus on which sequencing technology is most effective for quality control of lentiviral vectors, and current cDNA sequencing approaches which rely on reverse transcription (RT) of the lentiviral RNA can introduce bias (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work aimed at improving the performance of HIV-based lentiviral vectors showed that they can be created using minimal HIV-1 sequences by deleting most of the gag and over 50% of the env regions, ultimately improving the safety of these vectors. 55 …”
Section: Introductionmentioning
confidence: 99%